Investigating growing inequality in Mozambique - Carlos Gradín; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
In this paper, we investigate the long-term trend of consumption inequality in Mozambique. We show that an imbalanced growth path disproportionally benefited the better-off and caused increasing inequality, especially in more recent years, curbing the necessary reduction in poverty. Using a regression decomposition technique, our results suggest that this trend was strongly associated with the higher attained education of household heads and with changes in the structure of the economy (with less workers in the public and subsistence sectors). The trend was, however, mitigated by the tendency for the higher level of attained education and the smaller public sector to become associated with less inequality over time. These results point to the importance of accelerating the expansion of education and improving the productivity of the large subsistencesector to lower inequality in line with the sustainable development goals.
Keywords: D63; I24; O55; 330; inequality; Mozambique; decomposition; RIF